On the bilateral trade effects of free trade agreements between the EU-15 and the CEEC-4 countries - Guglielmo Maria Caporale; Christophe Rault; Robert Sova; Anamaria Sova (Center for Economic Studies and ifo Institute (CESifo), 2008)
The expansion of regionalism has spawned an extensive theoretical literature analysing the effects of Free Trade Agreements (FTAs) on trade flows. In this paper we focus on FTAs (also called European agreements) between the European Union (EU-15) and the Central and Eastern European countries (CEEC-4, i.e. Bulgaria, Hungary, Poland and Romania ) and model their effects on trade flows by treating the agreement variable as endogenous. Our theoretical framework is the gravity model, and the econometric method used to isolate and eliminate the potential endogeneity bias of the agreement variable is the fixed effect vector decomposition (FEVD) technique. Our estimation results indicate a positive and significant impact of FTAs on trade flows. This finding is robust to the inclusion in the sample of a group of control countries (specifically Belarus, the Russian Federation and Ukraine) that did not sign an FTA. Besides, we show that trade growth after the FTA agreement with the EU was signed exceeded trade growth of the control group of countries which did not become members.
Keywords: E61; F13; F15; C25; 330; Trade policy; Handelsregionalismus; Europäische Integration; Freihandelszone; Außenhandelseffekt; Gravitationsmodell; Panel; Regression; Osteuropa; EU-Staaten